(3MbGFb GldEjeGfs - (3GdYGedj GdLYHj, GdYGedj GdLYHj, Rjf GdOjf Hf Ydj Hf CMeO, (B966 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3aEfj deG QCjJ GdCbhGd aj MbjbI GdEjeGf eY GdGJaGb Ydi MbjbJg eJcKQI hGdCOdI Ydi Pdc aj cJH GdCUhd efJTQI hCcKQg dG jQhj GdZdjd hdG jTaj GdYdjd hdG jLOj efgG EdG Gdbdjd CMHHJ Cf GLeY efgG LedI cGajI (B...s
(3BNQgG (B:s
... (3hGdejRGf gd gh ejRGf MbjbI Ch cfGjI Yf GdYOd Edi ZjQ Pdc ef GdJaGUjd GdJj WQjbgG GdBMGO aGdXGgQ Cf GdLgd HgG ZjQ eNd HGdEjeGf hcPG chf Lfge fYhP HGddg efgG JMJ GdCQV Gh chf GdLfI ahb GdSeGA (B.s
(3JHUQI GdYfhGf (B:s
(3hjSei (B: (3GdGjeGf hGdGSdGe h MajaI GdGjeGf hGdGSdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3dCYdGe (B3\ 64s
(3GdPQjYI (B7 \ 155s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds